Assessing visitor preferences and willingness to pay for Marine National Park Hikkaduwa: application of choice experiment method - Jayaratne, Chamathi; Gunawardena, U. A. D. P.; Edirisinghe, Jagath; Dissanayake, Sahan; Rajapaksha, Darshana (National Science Foundation: Colombo, 2023)
Eco-tourism all over the world is threatened by the fact that the coral reefs and associated ecosystems are in a process of disappearing at an accelerated rate due to several natural and anthropogenic causes. In this context, the MarineNational Park Hikkaduwa (MNPH), one of the four marine national parks in Sri Lanka, that features a fringing coral reef with a high degree of biodiversity, reports a decreasing trend in visitation mainly due to a condition of coral bleaching caused by an El Nino effect. Unfortunately, the regeneration of the corals is found to be slowed by continuous anthropogenic activities. Against this background, the research focuses on investigating how visitor behaviour changes with the degraded situation and what avenues are available to attract more visitors to ensure benefit flows. In this concern, visitor preferences regarding the quality of the habitats and other facilities and their significance were analysed under a conditional logistic regression model. Further, a choice experiment was carried out with a randomly selected group of 200 visitors to diagnose their response to the present condition of the coral reef, the beach, and the facilities provided. Under a conditional logistic model, it was discovered that the condition of the coral reef is an important attribute that answers the question of why visitors are not willing to pay if the corals are bleached and broken. It was also discovered that the visitors are willing to pay LKR 322.52 if they are provided with new boats and new safety jackets. The results indicate that benefit flows could be enhanced with the restoration of coral ecosystems and the improvement of the physical infrastructure. Overall, the research attempts to establish that the standard maintenance of the coral reef along with high-quality visitor welfare facilities to match visitor preferences will positively impact all types of payment compliance issues with regard to the visitors.
Keywords: Coral reef; Choice experiment; Willingness to pay